Archaeomagnetic dating as a tool to overcome the Hallstatt plateau: A combined chronological approach at the salt production site of Piscina Torta (Rome, Italy) - Luca Alessandri; Anita Di Chiara; Raquel Bonilla-Alba; Luca Cusimano; Giovanni Alberto Della Sala; Angelica Fiorillo; Virginia Gianni; Caterina Rossi; Agostino Sotgia; Fabio Florindo (PLoS ONE, 2026)
The salt production site of Piscina Torta (Rome, Italy) presents a complex chronological challenge due to its ceramic assemblage, which is almost exclusively represented by coarse ware jars with limited morphological variability. Furthermore, its occupation period coincides with the Hallstatt plateau, which hampers radiocarbon dating resolution. This study addresses these limitations by applying archaeomagnetic analyses to a kiln and ceramic fragments both from Area 1 of the site. Archaeomagnetic dating based on directions from the kiln and on archaeointensity from pottery sherds yielded two-time intervals: 930–755 BCE and 740–700 BCE. These results confirm the potential of this method as a viable dating tool, especially for problematic radiocarbon periods. At Piscina Torta, the integration of archaeomagnetic, typo- chronological, and radiocarbon data enabled the subdivision of Area 1 into three occupational phases: Phase A (725–710 BCE), Phase B (710–550 BCE), and Phase C (550–525 BCE). This study demonstrates the effectiveness of archaeomagnetism in enhancing chronological resolution in early first-millennium BCE contexts and highlights its important contribution when combined with traditional dating methods.